PEMANFAATAN TEPUNG AMPAS TAHU DENGAN PENAMBAHAN PISANG AMBON SALE DALAM PEMBUATAN SNACK BARS - Dila Yudasri; Ahkyar Ali; Dewi Fortuna Ayu (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to get the best composition of okaraflour and ambonbanana sale for makingsnack bars.The study used a Completely Randomized Design (CRD) with 5 treatments and 3 replications.The treatments wereokara flour and ambonbanana sale 90%:10%,80%:20%,70%:30%, 60%:40%, and 50%:50%. Data were statistically analyzed using Analysis of Variance (ANOVA) and followed by Duncan’s New Multiple Range Test(DNMRT) test at 5% level. Results of the analysis showed that increase of okara flourand ambon banana sale significantlyaffected on moisture, ash, fat, protein, carbohydrate, and crude fiber content as well as descriptive and hedonic sensory tests, such as of color, aroma, flavor, taste, texture, and overall assessment of the snack bars.Based on this research the best treatment wassnack barsfrom okara flourand ambon banana sale 50%:50%which hadmoisture 10.67%, ash 2.47%,fat 24.60%, protein10.25%, carbohydrate52.01%,and crude fiber content 15.77%. Result of the descriptive test of the snack bars from the best treatment was a brownish yellow, ambon banana sale taste and aroma, and densely and softly texture. Result of thehedonic test on color, aroma, taste, texture, and overall assessmentwere liked by panelists. Keywords:snack bars, okara flour, and ambon banana sale.